Integrative mapping reveals molecular features underlying the mechanism of nucleocytoplasmic transport - Barak Raveh; Roi Eliasian; Shaked Rashkovits; Daniel Russel; Ryo Hayama; Samuel Sparks; Digvijay Singh; Roderick Y. H. Lim; Elizabeth Villa; Michael P. Rout; David Cowburn; Andrej Sali (Proceedings of the National Academy of Sciences, 2025)
Nuclear pore complexes (NPCs) enable rapid, selective, and robust nucleocytoplasmic transport. To explain how transport emerges from the system components and their interactions, we used experimental data and theoretical information to construct an integrative Brownian dynamics model of transport through an NPC, coupled to a kinetic model of transport in the cell. The model recapitulates key aspects of transport for a wide range of molecular cargoes, including preribosomes and viral capsids. Our model quantifies how flexible phenylalanine-glycine (FG) repeat proteins create an entropic barrier to passive diffusion and how this barrier is selectively lowered in facilitated diffusion by the many transient interactions of nuclear transport receptors with the FG repeats. Selective transport is enhanced by “fuzzy” multivalent interactions, redundant FG repeat mass, coupling to the energy-dependent RanGTP concentration gradient, and exponential dependence of transport kinetics on the transport barrier. Our model will facilitate rational modulation of the NPC and its artificial mimics.